Sistem Kebudayaan Pada Masyarakat Madinah di Era Nabi Muhammad SAW - Handayani, Irma; Daulay, Haidar Putra; Sumanti, Sholihah Titin (Innovative: Journal Of Social Science Research, 2025)
Cultural System in Medina Society in the Era of the Prophet Muhammad SAW ". The main focus of this research is the process of the Prophet Muhammad's hijrah. to Medina, the Prophet's establishment of the Medina Charter system as a system for empowering the people of Madinah and about the cultural systems in Medina during the time of the Prophet Muhammad. The problem formulation in this research is: 1) What is the concept of the Prophet Muhammad's migration to Medina? 2) How was the Prophet Muhammad SAW determined. in the Medina charter system as a community empowerment system in Medina? 3) What were the cultural systems in Medina during the time of the Prophet Muhammad SAW? The method used in this research is a qualitative method with a library research approach. Data sources for this research include books on the History of Islamic Culture/Civilization, as well as scientific works from the Medina period.